2008
DOI: 10.1002/crat.200711045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface tension‐driven flow on BaB2O4 crystal growth from high temperature melt‐solution

Abstract: The surface tension driven-flow in BaB 2 O 4 (BBO) melt-solution is visualized by differential interference microscope coupled with Schlieren technique, and the streamline of the steady thermocapillary convection is found to be in form of an axially symmetric pattern. Based on the observation of BBO crystal rotation caused by the convective vortex, the widths of interfacial concentration, heat and momentum boundary layer are calculated. The effect of thermocapillary convection on boundary layer thickness is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The Marangoni effect [1][2][3] is a general term for a family of flows induced by some interfacial tension gradient associated with either chemical [4] or thermal [5] gradients with numerous applications and ramifications [5][6][7][8][9][10][11][12][13][14]. In this study we focus on chemically induced Marangoni flow, for which one can distinguish between two different but related systems:…”
Section: Introductionmentioning
confidence: 99%
“…The Marangoni effect [1][2][3] is a general term for a family of flows induced by some interfacial tension gradient associated with either chemical [4] or thermal [5] gradients with numerous applications and ramifications [5][6][7][8][9][10][11][12][13][14]. In this study we focus on chemically induced Marangoni flow, for which one can distinguish between two different but related systems:…”
Section: Introductionmentioning
confidence: 99%
“…Time traces of normal growth rate V , step velocity υ, and local growth rate R for the {1010} interface.along the heater, d is the characteristic length of the liquid, η is the dynamic viscosity, and κ is the thermal diffusivity. For a coarse estimate[12], the value of M a is about 20 in present solution system, which cannot trigger oscillatory Marangoni Step bunching showing the interfacial instability of a vicinal face.…”
mentioning
confidence: 73%
“…Furthermore, the value of dimensionless Marangoni number Ma = σ T ΔTd/ηκ characterizing the strength of thermocapillary convection was also calculated for investigating the effect of Marangoni flow. Here σ T = dσ/dT is the temperature coefficient of surface tension σ, ΔT is the horizontal temperature difference X. H. Pan et al flows for BBO solution according to the discussions in our previous work [12,13].…”
Section: Fluctuations In Growth Rate and Observation Of Step Bunchingmentioning
confidence: 99%
“…Flow instabilities in an evaporating liquid appear in a variety of industries and applications, including crystallization [1,2], heat pipe cooling [3][4][5], particle self-assembly on surfaces [6,7], welding [8,9], spray cooling [10] and design of biosensors [11]. Quantification of the flow field and visualization of the convective structure of these instabilities has been the subject of several studies since the seminal work of Bénard [12] who observed a regular pattern of convective cells inside an evaporating thin liquid film with a free upper surface that was heated from the bottom.…”
Section: Introductionmentioning
confidence: 99%